1878 Cal Stat. 117, An Act Amending Section Four Hundred and Fifteen of the Penal Code, in Relation to Crimes Against The Public Peace, ch. CCXCIX, § 1 - (:unkn) unknown (General Publisher, 1878)
Prohibited discharge of any gun or pistol in an unincorporated town. Violators fined not exceeding two hundred dollars, or imprisonment not exceeding ninety days, or both fine and imprisonment.
--
Keywords: DISCHARGE